Feasibility of 68Ga-labeled Siglec-9 peptide for the imaging of acute lung inflammation: a pilot study in a porcine model of acute respiratory distress syndrome - Jaime Retamal; Jens Sörensen; Mark Lubberink; Fernando Suarez-Sipmann; João Batista Borges; Ricardo Feinstein; Sirpa Jalkanen; Gunnar Antoni; Göran Hedenstierna; Anne Roivainen; Anders Larsson; Irina Velikyan (United States, 2022)
There is an unmet need for noninvasive, specific and quantitative imaging of inherent inflammatory activity. Vascular adhesion protein-1 (VAP-1) translocates to the luminal surface of endothelial cells upon inflammatory challenge. We hypothesized that in a porcine model of acute respiratory distress syndrome (ARDS), positron emission tomography (PET) with sialic acid-binding immunoglobulin-like lectin 9 (Siglec-9) based imaging agent targeting VAP-1 would allow quantification of regional pulmonary inflammation. ARDS was induced by lung lavages and injurious mechanical ventilation. Hemodynamics, respiratory system compliance (Crs) and blood gases were monitored. Dynamic examination using [15O]water PET-CT (10 min) was followed by dynamic (90 min) and whole-body examination using VAP-1 targeting 68Ga-labeled 1,4,7,10-tetraaza cyclododecane-1,4,7-tris-acetic acid-10-ethylene glycol-conjugated Siglec-9 motif peptide ([68Ga]Ga-DOTA-Siglec-9). The animals received an anti-VAP-1 antibody for post-mortem immunohistochemistry assay of VAP-1 receptors. Tissue samples were collected post-mortem for the radioactivity uptake, histology and immunohistochemistry assessment. Marked reduction of oxygenation and Crs, and higher degree of inflammation were observed in ARDS animals. [68Ga]Ga-DOTA-Siglec-9 PET showed significant uptake in lungs, kidneys and urinary bladder. Normalization of the net uptake rate (Ki) for the tissue perfusion resulted in 4-fold higher uptake rate of [68Ga]Ga-DOTA-Siglec-9 in the ARDS lungs. Immunohistochemistry showed positive VAP-1 signal in the injured lungs. Detection of pulmonary inflammation associated with a porcine model of ARDS was possible with [68Ga]Ga-DOTA-Siglec-9 PET when using kinetic modeling and normalization for tissue perfusion.